1984
DOI: 10.1159/000173677
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognostic Significance of Symptomatic and Asymptomatic Exercise-Induced Ischemia in Patients with Recent Myocardial Infarction

Abstract: To determine the incidence and the significance of anginal chest pain during abnormal exercise testing (⇓S-T ≧ 0.1 mV) in patients with recent myocardial infarction we reviewed a series of 353 patients who underwent maximal bicycle exercise stress 4–8 weeks following acute myocardial infarction. Of the 353 patients, 26 had ischemic ECG changes and chest pain (group A); 85 patients had ischemic ECG changes but no chest pain (group B). The two groups differ significantly only in the frequency of a history of typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Much controversy persists regarding the usefulness of using exercise‐induced symptomatic myocardial ischaemia as a parameter for risk stratification following AMI [10–16]. Opasich et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much controversy persists regarding the usefulness of using exercise‐induced symptomatic myocardial ischaemia as a parameter for risk stratification following AMI [10–16]. Opasich et al .…”
Section: Discussionmentioning
confidence: 99%
“…Opasich et al . [10] studied 353 patients who underwent maximal bicycle exercise stress testing 4–8 weeks following AMI. They concluded that the occurrence of angina pectoris associated with ST‐segment depression did not increase the risk of subsequent cardiac events during a mean follow‐up of 29 ± 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…signs of ischemia without angina pectoris, has been questioned [1][2][3][4][5][6]. Reports addressing this subject have especially focussed on the difference in future cardiac risk among patients with symptomatic angina pectoris compared to patients without symptoms [2,4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%